Comparison of the diagnostic accuracy of contrast‐enhanced MRI and diffusion‐weighted MRI in the differentiation between uterine leiomyosarcoma / smooth muscle tumor with uncertain malignant potential and benign leiomyoma. Issue 2 (18th September 2015) - Lin, Gigin; Yang, Lan‐Yan; Huang, Yu‐Ting; Ng, Koon‐Kwan; Ng, Shu‐Hang; Ueng, Shir‐Hwa; Chao, Angel; Yen, Tzu‐Chen; Chang, Ting‐Chang; Lai, Chyong‐Huey
Abstract : Purpose: To compare the diagnostic accuracy of contrast‐enhanced (CE) magnetic resonance imaging (MRI) and diffusion‐weighted MRI (DWI) in the differentiation between uterine leiomyosarcoma (LMS) / smooth muscle tumor with uncertain malignant potential (STUMP) and benign leiomyoma. Materials and Methods: A consecutive cohort of 8 LMS/STUMP and 25 benign leiomyomas underwent pelvic MRI exam at 3T. Two radiologists independently evaluated images based on CE‐MRI (central nonenhancement at equilibrial phase) and DWI (hyperintensity on b = 1000 s/mm 2 and hypointensity on apparent diffusion coefficients [ADC] map). The ADC values were calculated from b = 0 and 1000 s/mm 2 . Results: CE‐MRI yielded a significantly superior diagnostic accuracy (0.94 vs. 0.52) and a significantly higher specificity (0.96 vs. 0.36) than DWI ( P < 0.05 for both), and remained a comparably high sensitivity as DWI (0.88 vs. 1.00). A combination of DWI and ADC value <1.08 × 10 −3 mm 2 /s (determined by receiver operating characteristic analysis) improved diagnostic accuracy, sensitivity, and specificity of DWI to 0.88, 0.88, and 0.88, respectively, by post‐hoc analysis based on the same study cohort. Conclusion: For prospective differentiation between uterine LMS/STUMP and benign leiomyoma, CE‐MRI can provide accurate information and is preferable to DWI. Combination of DWI and ADC values can achieve a comparable diagnostic accuracy to CE‐MRI. J. Magn. Reson. Imaging 2016;43:333–342.